Evaluation of novel approaches to software engineering : 11th International Conference, ENASE 2016, Rome, Italy, April 27-28, 2016, Revised selected papers /: 11th International Conference, ENASE 2016, Rome, Italy, April 27-28, 2016, Revised selected papers. (2016) - Unknown
No abstract available